2021
DOI: 10.17582/journal.sja/2021.37.3.722.734
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Variability in F4 Populations of Upland Cotton (Gossypium hirsutum L.)

Abstract: P akistan is the 4 th largest cotton producing and 3 rd cotton consuming country, however, the yield is low as compared other cotton producing countries (Nazir et al., 2020). The main reason of low yielding potential of existing germplasm is influence of biotic and abiotic factors and cotton production can be manage by introduction of new cotton varieties. Pakistan is leading in exporting cotton yarn and third in the export of raw material of the cotton crop worldwide (Nizamani et al., 2017). The nation of Pak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Ginning out turn was found maximum in the parent MCU 5 (39.72%) and the cross CO 14 x GISV 328 (39.34%). This result was supported by Ahsan et al (2015), Khokhar et al (2017), Baloch et al (2018), Abro et al (2021) and Muhammed et al (2016) for seed cotton yield.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Ginning out turn was found maximum in the parent MCU 5 (39.72%) and the cross CO 14 x GISV 328 (39.34%). This result was supported by Ahsan et al (2015), Khokhar et al (2017), Baloch et al (2018), Abro et al (2021) and Muhammed et al (2016) for seed cotton yield.…”
Section: Resultssupporting
confidence: 62%
“…This indicates that heritability is due to additive gene action and hence direct selection will be profitable in these traits. Previous studies bySahar et al (2021),Abro et al (2021),Nandhini et al (2019), Nikhil et al (2018 andShao et al (2016) documented similar results. Higher heritability with medium genetic advance was found for days to 50 per cent flowering (66.77 %, 10.85 %), plant height (80.90 %, 15.97 %), seed index (72.67 %, 12.53 %) and fibre strength (83.20 %, 13.36 %).…”
supporting
confidence: 67%
“…Batool et al, ( 2010) reported similar ndings for days to rst owering. Plant height is important symbol which permits the yield plant to resist clearly with weeds and other purposes such as proper distribution of photosynthesis CRIS-508 x CRIS-510 was reported with taller plants, while variety CRIS-508 reported taller Plant among the parental lines Abro et al (2021) reported almost similar ndings for plant height in F4 combinations and their parents. Sympodial branches were noted in maximum number in F2 hybrid Bakhtawar x Koonj whereas genotype CRIS-510 was remained on the top among the parents.…”
Section: Mean Comparison For Quantitative Charactersmentioning
confidence: 97%
“…Farooq et al (2018) and Saleem et al (2020) carried out research in various cotton genotypes for estimating genetic and inheritance of quantitative characters utilizing numerous segregating progenies in which they indicated that the segregating progenies provided more genetic perception into polygenic parameters such as bolls per plant, boll size and boll weight. Abro et al (2021) reported moderate to high heritability with low genetic gain for boll weight in F4 populations of upland cotton. In case of seed cotton yield moderate to high heritability observed with low to high genetic progression.…”
Section: Estimation Of Heritability and Genetic Advancementioning
confidence: 99%